RETRACTED: The world of subjects in "Nazm Ul-Javahir" by Alisher Navai - Rajabova Marifat; Safarova Hilola; Amonova Zilola; Shirinova Mekhrigiyo; Ibotova Madina (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001